2017
DOI: 10.1126/science.aam6622
|View full text |Cite
|
Sign up to set email alerts
|

Quantized thermal transport in single-atom junctions

Abstract: Thermal transport in individual atomic junctions and chains is of great fundamental interest because of the distinctive quantum effects expected to arise in them. By using novel, custom-fabricated, picowatt-resolution calorimetric scanning probes, we measured the thermal conductance of gold and platinum metallic wires down to singleatom junctions. Our work reveals that the thermal conductance of gold single-atom junctions is quantized at room temperature and shows that the Wiedemann-Franz law relating thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
241
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(266 citation statements)
references
References 53 publications
20
241
1
4
Order By: Relevance
“…We expect that our predictions can soon be verified experimentally by using techniques similar to those developed in Ref. 37.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We expect that our predictions can soon be verified experimentally by using techniques similar to those developed in Ref. 37.…”
Section: Discussionmentioning
confidence: 96%
“…However, it is worth stressing that this appealing suggestion was made without taking into account the phonon contribution in the ab initio calculations and without measuring the thermal conductance. Indeed experimental setups were until recently not sensitive enough to measure κ at the atomic scale, and single-molecule junctions have yet to be examined with newly developed tools [37]. Thus, this interesting suggestion still has to stand careful theoretical and experimental tests with access to all the major quantities determining the figure of merit.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we also show that similar concepts apply to the case of OPE3 and, in particular, we find a clear difference between para-and meta-OPE3, where the central benzene ring is connected in para or meta position. Our work provides concrete predictions that can potentially be tested, given the recent experimental advances in the measurement of the thermal conductance of atomic-scale contacts 52,53 . In addition, it sheds light on the importance of phonon interference effects to tune the thermal transport of molecular junctions.…”
Section: Introductionmentioning
confidence: 99%
“…This situation has now changed, and two experimental groups have finally been able to independently explore the thermal transport in atomic contacts [23,24]. In particular, Cui et al [23] were able to measure the room-temperature thermal conductance of both Au and Pt contacts and found that in the case of Au single-atom contacts the thermal conductance is quantized in units of the universal thermal conductance quantum κ 0 = π 2 k 2 B T /(3h), where T is the absolute temperature. Before this, thermal conductance quantization had already been reported in a series of experiments, making use of different microdevices, where the heat was carried by phonons, electrons, or photons [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%